Pembelajaran Kitab Kuning Pada Program Akselerasi di Madrasah Diniyyah Al Amriyyah Blokagung Banyuwangi Tahun Ajaran 2023/2024 - Maulidi, Irfan; Lestari, Maghfirotul Firmaning (IJIT: Indonesian Journal of Islamic Teaching, 2023)
ABSTRACT Multiculturalism in Indonesia is based on the 1945 Constitution article 28 paragraphs 1 and 2 which state that the Indonesian nation and society consist of various ethnic groups that are committed to build Indonesia as a nation-state. SDN Puger Kulon 01 Jember has racial, ethnic and cultural diversity. Therefore, they become very interesting to be studied. Since, by this multiculturalism, teachers at SDN Puger Kulon 01 Jember have learning strategies in the form of direct instruction strategies, interactive instruction strategies, and experiential learning strategies in instilling multiculturalism values at SDN Puger Kulon 01 Jember. The foci of this research are: 1) How is the Strategy of Islamic Religious Education Teacher in instilling multicultural values of Pluralism at SDN Puger Kulon 01 Jember? 2) How is the Strategy of Islamic Religious Education Teacher in instilling Democratic multicultural values instilled at SDN Puger Kulon 01 Jember? 3) How is the Strategy of Islamic Religious Education Teacher in instilling multicultural values of Humanism at SDN Puger Kulon 01 Jember? This research used 1) descriptive qualitative and phenomenological research type. 2) Research location. 3) The presence of researchers. 4) Research subjects: purposive sampling technique. 5) Source of data. 6) The data were collected by interviews, observation, and documentation. 7) The data were analyzed through three steps: data reduction, data presentation, conclusion drawing and data verification. 8) Data validity by using source and technical triangulation. 9) Stages of research. The research findings indicate that: 1) in instilling the values of pluralism, teachers use direct teaching strategies and the Take and Give learning model. 2) in instilling democratic values, teachers use interactive teaching strategies and the Problem Based Learning model. 3) in instilling humanistic values, teachers use experiential learning strategies and the Cooperative Learning model.